THE MYTHOLOGICAL ORIGIN IN THE POETRY OF K.D. BALMONT - Goncharova Nina Vasilyevna (Western European Studies, 2024)
The article attempts to look at Balmont's work from a mythological point of view, to evaluate it in order to revive mythological thinking as the primary basis of creativity; mythological images and motifs in K.D. Balmont's poetry are analyzed. Despite the available research, the question of Balmont's mythologism still remains open
Keywords: symbol; myth; myth-thinking; ancient culture